(3GdQSGdI GdTeSjI aj GdCUhd GdMSGHjIs - (3GdfXGe GdfjSGHhQj , GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQj, fXGe GdOjf GdCYQL,J (B850 (3g` s
(3ChdgG (B:s
(3hHYO aEf CMhL Ndb Gddg Edjg GdMSf Hf eMeO GdfjSGHhQi jbhd GdMSGH Yde dG fcGO jSJZfi Yfg WdGH GdYdhe hGdBOGH s
(3BNQgG (B:s
(3GdGMJeGd GdZdW aiGdMSGH hai GdhRf JeJ GdQSGdg GdTeSjI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1062s
Keywords: (3GdQjGVjGJs